Adult Learners and the Identities They Tell: Pedagogic Spaces for Inviting New Tales - Andrew Wojecki (Adult Education Research Conference, 2007)
Adult learners often tell and retell their stories of learning. These previous experiences, encounters, and histories of learning are significant in the construction of adult learners’ identities, biographies, and relationships to learning. Narrative perspectives of identity invite adult educators in considering how their educative practices enable adult learners in further ‘storying’ themselves as active participants in learning, both within the lifeplace and workplace.